Milton's loves : from amity to caritas in the Paradise epics - Paice, Rosamund (New York, NY : Routledge, 2023)
"This book is about the multiple loves of Paradise Lost and Paradise Regained: sanctioned loves and outlawed loves, sincere loves and false loves, Christian loves, classical loves, humanist loves, and love as emotion. In showing how these loves motivate the most significant actions of the Paradise epics, it reveals Milton to have made creative use of the tensions between philosophical ideals, social conventions, and the rather messier ways in which love emerges in practice. Love, so central to Milton's view of Edenic joy and obedience to God, unsettles earthly and heavenly communities, and is the origin of Miltonic transgression. Milton's Loves sheds new light on some of the most prominent concerns of Milton scholarship, including: why Milton's God is so difficult for readers to connect to; Satan's apparent heroism; Milton's radical theology; and the nature of Milton's muse. It is a book that will appeal to students and scholars of Milton and early modern studies more broadly, and is structured in a way that will aid easy reference"--
Keywords: Milton, John, -- 1608-1674.; Milton, John, -- 1608-1674.; Love in literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh